PERAN MEDIA MASSA DALAM KOMUNIKASI POLITIK DI INDONESIA - Herdiansyah Amanu; Leti Karmila (Jurnal Ilmu Komunikasi Balayudha, 2021)
The development of mass media in Indonesia has experienced tremendous growth. Especially after entering the reformation era, the tap of democracy in Indonesia has begun to open. This turned out to have a tremendous impact on press freedom. The press is no longer confined by the rules of the authorities, so that the press can be used by various parties to defend the interests of the institutions that own it, including for political interests. The trend that is currently seen is that social-political organizations in Indonesia are starting to compete to dominate media companies in order to improve their image in the eyes of the public. The political elites try to build political communication intensely in order to attract the sympathy of the masses to side with them. The media is so sought after by many parties because of its power in shaping public opinion.